Upaya Meningkatkan Hasil Belajar Matematika dengan Pendekatan Contextual Teaching and Learning (CTL) pada Siswa Kelas V Semester I Tahun Pelajaran 2019– 2020 di SDN 2 Setanggor - Wirya, Baiq Sri Olati (MASALIQ, 2021)
This study aims to improve student's learning outcomes in solving mixed calculation problems with contextual teaching and learning (CTL) approaches. This research method is a type of classroom action research. This class action research was conducted at SD Negeri 2 Setanggor which is addressed to Lendek Village, Sukamulia sub-district. The implementation of this study was carried out in class V of the 2019/2020 school year with a total of 27 students. Based on the discussion of the results of the cycle I and cycle II research it can be concluded that using car-car props on the calculation of integer calculation operating materials with contextual teaching and learning (CTL) approach, can improve student learning outcomes this is proven: In cycle, I the number of students completed on the main operation calculates integers (addition and subtraction) with contextual teaching and learning (CTL) approach is 66% or 18 of the 27 students. In cycle II, the percentage of student completion experienced improvements with the contextual Teaching and Learning (CTL) approach which is as much as 85% or 23 out of 27 students.